Mordeduras de perros y medidas preventivas aplicadas por estudiantes de secundaria en Cusco, Perú, en 2024 - Ccansaya V., Lucero (2025)
The aim of this study was to describe dog bite accidents and knowledge of preventive measures among 4th and 5th year secondary school students at three educational institutions in the province of Cusco (Cusco, Peru) in 2024. A survey was conducted with 566 students. Results showed that 60.8% reported having suffered a dog bite accident; 44.5% had suffered one bite more than 5 years ago; 66.0% of the bites occurred on public roads; and 77.3% were unprovoked. Of those bitten, 66.9% suffered only one bite, but only 23.5% of those bitten went to a medical center. Moreover, 76.7% washed the wound, 64.0% recognized the attacking dog, 65.7% did not know if the dog was vaccinated and 95.5% knew that rabies is a disease transmitted by dog bites. It is important for students to know that after a bite, they should wash the wound, identify the biting animal, and go to the nearest health center, especially given that this disease is present in departments bordering Cusco.